Wireless home security system using GSM / Mohd Fahmy Ismail - Ismail, Mohd Fahmy (2012)
This thesis present wireless security network for home based on GSM. The purpose of this work is to design and develop a home security system that can give security against theft or any violence that happen in home by using wireless technology. The hardware of this system includes PIC 16F877, magnetic sensor and GSM modem and mobile phone. The system programmed using assembly language which make it able to receive signal and can send short message service (SMS) to the user's mobile phone when any security area has been invaded. The system use GSM technology which is provides any access to the security control